Improvement of Pulmonary Function by Oral Treatment with a VLA-4 Antagonist in a Mouse Asthmatic Model - Gensuke Takayama; Keiko Matsumoto; Tomoe Taira; Misato Aonuma; Mika Yokoyama; Yutaka Iigo; Tohru Takashi (Elsevier, 2013)
We investigated in vivo efficacies of the newly synthesized VLA-4 antagonist Compound A {trans-4-[1-[[2,5-Dichloro-4-(1-methyl-3-indolylcarboxamido)phenyl]acetyl]-(4S)-methoxy-(2S)-pyrrolidinylmethoxy]cyclohexanecarboxylic acid} on Ascaris antigen-induced airway inflammation and hyperresponsiveness in a murine asthmatic model. Oral administration of Compound A significantly inhibited eosinophil infiltration into BALF and airway hyperresponsiveness 48 h after the antigen challenge. Histologic analysis of the lung sections confirmed the BALF result and revealed suppression of edema and mucus hyperplasia at 8 and 48 h after the challenge, respectively. These findings clearly show that orally active Compound A has therapeutic potential for treatment of asthma. Keywords:: VLA-4, eosinophil, airway hyperresponsiveness